Activatable Mitochondria‐Targeting Organoarsenic Prodrugs for Bioenergetic Cancer Therapy. Issue 3 (13th November 2020) - Luo, Xiangjie; Gong, Xuanqing; Su, Liyun; Lin, Hongyu; Yang, Zhaoxuan; Yan, Xiaomei; Gao, Jinhao
Abstract: Despite widespread applications for cancer treatment, chemotherapy is restricted by several limitations, including low targeting specificity, acquired drug resistance, and concomitant adverse side effects. It remains challenging to overcome these drawbacks. Herein, we report a new bioenergetic approach for treating cancer efficiently. As a proof‐of‐concept, we construct activatable mitochondria‐targeting organoarsenic prodrugs from organoarsenic compounds and traditional chemotherapeutics. These prodrugs could accomplish selective delivery and controlled release of both therapeutic agents to mitochondria, which synergistically promote mitochondrial ROS production and induce mitochondrial DNA damage, finally leading to mitochondria‐mediated apoptosis of cancer cells. Our in vitro and in vivo experiments reveal the excellent anticancer efficacy of these prodrugs, underscoring the encouraging outlook of this strategy for effective cancer therapy. Abstract : Activatable mitochondria‐targeting organoarsenic prodrugs have been constructed for bioenergetic cancer therapy. These prodrugs are capable of selective co‐delivery and controlled release of organoarsenicals and chemotherapeutics to mitochondria, which synergistically promote mitochondrial ROS production and induce mitochondrial DNA damage, resulting in the mitochondria‐mediated apoptosis of cancer cells.